2017
DOI: 10.1016/j.rdc.2017.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Human Leukocyte Antigen–Disease Associations in Rheumatoid Arthritis

Abstract: The etiology and pathogenesis of rheumatoid arthritis (RA) are influenced by environmental and genetic risk factors. Shared epitope-coding HLA-DRB1 alleles increase RA risk and severity; however, the underlying mechanisms of action remain unclear. In contrast, several other DRB1 alleles protect against RA. Additionally, genome-wide association studies suggest that RA associates with other, HLA and non-HLA, genes but the relative contributions of such risk loci to RA are incompletely understood. Future research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(64 citation statements)
references
References 103 publications
(103 reference statements)
1
57
0
6
Order By: Relevance
“…In rheumatic diseases, a human leukocyte antigen (HLA)-restricted T cell response to antigen has been shown to affect disease progression, with several HLA alleles associated with disease severity. 3 It was revealed that HLA-DRB1*11 and variant major histocompatibility complex (MHC) class II contributed to the development of JIA, while a “shared epitope” encoded by HLA-DRB1 alleles was correlated with the typical characteristics of both JIA and rheumatoid arthritis (RA). An expressions of HLA-DR4 and HLA-DRw6+ were correlated with articular symptoms in patients with AOSD.…”
Section: Introductionmentioning
confidence: 99%
“…In rheumatic diseases, a human leukocyte antigen (HLA)-restricted T cell response to antigen has been shown to affect disease progression, with several HLA alleles associated with disease severity. 3 It was revealed that HLA-DRB1*11 and variant major histocompatibility complex (MHC) class II contributed to the development of JIA, while a “shared epitope” encoded by HLA-DRB1 alleles was correlated with the typical characteristics of both JIA and rheumatoid arthritis (RA). An expressions of HLA-DR4 and HLA-DRw6+ were correlated with articular symptoms in patients with AOSD.…”
Section: Introductionmentioning
confidence: 99%
“…Second, studies have suggested that AR and RA may share overlapping genetic predisposition since certain genetic variations in immune‐related genes have been linked to increased susceptibility to both AR and RA. For instance, polymorphisms in HLA‐DRB1, TLR4, and CD14 genes are known to be associated with susceptibility to RA and other autoimmune diseases 31,32 . These genes are also shown to be associated with AR‐based on candidate gene association studies 33‐35 …”
Section: Discussionmentioning
confidence: 99%
“…The physiopathology of RA can be described in three phases: i) the triggering of the autoimmune reaction ii) the inflammation and iii) the osteocartilaginous destruction. A major component of genetic susceptibility to RA can be explained by the inheritance of the HLA-DRB1 allele which starts the autoimmune reaction (van Drongelen & Holoshitz, 2017). Particularly, the expression of the HLADRB1*01 and *04 alleles corresponding to the shared epitope induces the presence of the HLA class II molecule on the surface of antigen-presenting cells recognizing the antigens responsible for the immune reaction of RA ( Figure 1) (Roudier, 2000).…”
Section: Physiopathology Of Rheumatoid Arthritismentioning
confidence: 99%